2000
DOI: 10.1002/1097-0320(20001015)42:5<284::aid-cyto5>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Standardized flow cytometric method for the accurate determination of platelet counts in patients with severe thrombocytopenia

Abstract: Background: The therapeutic option of prophylactic platelet (PLT) transfusion in cases of severe thrombocytopenia critically depends on the availability of accurate and precise counts because clinical decisions are widely based on decision or trigger points. Although often applied in current practice at a level of 20 Gpt/L, there is increasing evidence that the trigger points could safely be reduced to10 or even 5 Gpt/L. In order to facilitate this downward revision, it is necessary to have PLT counting method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…In this study, as expected, the higher degree of correlation was observed between the CD61‐immunoplatelet and reference method, particularly in thrombocytopenic samples. These results therefore confirm the agreement between the flow cytometry and CD Sapphire immunoplatelet procedures, and according to other studies (Kunz et al. , 2000, 2001) provide evidence that the immunological method appear to be superior to the optical and impedance method in CD Sapphire.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, as expected, the higher degree of correlation was observed between the CD61‐immunoplatelet and reference method, particularly in thrombocytopenic samples. These results therefore confirm the agreement between the flow cytometry and CD Sapphire immunoplatelet procedures, and according to other studies (Kunz et al. , 2000, 2001) provide evidence that the immunological method appear to be superior to the optical and impedance method in CD Sapphire.…”
Section: Discussionsupporting
confidence: 89%
“…Another limitation is platelet count underestimation resulting from exclusion of larger platelet forms from conventional counting methods. Optical methods using two dimensions of light scatter, are less prone to these problems, but there are still some circumstances when optical analysis may also be erroneous (Kunz et al. , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The main conclusion of the study was that the CD61 ImmunoPLT method was more accurate than any other technology. This finding agrees with other studies comparing the CD61 method with the flow cytometric reference method but is not really unexpected because both immunological methods are essentially measuring the same parameter, albeit with a number of methodological differences (see above) (15)(16)(17)(18). Interestingly, the three optical methods were not shown to be superior to the impedance methods, agreeing with the recent study of Sandhaus et al (10).…”
Section: Large Multicentre Study On the Accuracy Of Platelet Countingsupporting
confidence: 92%
“…Immunoplatelet counting uses a platelet‐specific monoclonal antibody, most commonly CD61 or CD41, to identify the platelets in a whole blood sample for analysis with a flow cytometer. The immunoplatelet count has been used in studies, evaluating it against the other platelet counting methods, and the results from various groups have suggested that its use could potentially reduce the number of platelet transfusions used in supportive therapy (Dickerhoff & Von Ruecker, 1995; Harrison et al, 2000; Kunz et al, 2000). The immunoplatelet count has recently been shown to be suitable for use as the new reference method and has been recommended for use as such by the International Council for Standardization in Haematology (ICSH) (Harrison et al, 2001; ICSH Expert Panel on Cytometry and International Society of Laboratory Hematology Task Force on Platelet Counting, 2001).…”
mentioning
confidence: 99%